A Pharmacist Education Initiative Apoteker Cilik to Improve Medication Safety Knowledge among Elementary School Students in Gresik, Indonesia - Khoirotin Nisak; Zamrotul Izzah; Aniek Setiya Budiatin (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2022)
Pharmacists have the responsibility to ensure that medicines are obtained, used, stored, and disposed in the best and safest way particularly by a vulnerable population such as children. Pharmacists should adapt to a child’s level of health understanding to engage children in medication education. Therefore, a pharmacist-led program tailored to children in community settings was initiated in two elementary schools in Gresik, SD Muhammadiyah 1 Gresik and SD Muhammadiyah Manyar. An animated film Apoteker Cilik was shown to students of grade 4, 5, and 6 to promote the proper management of medications in line with the national campaign DAGUSIBU and to acquaint with the roles of pharmacists. A short questionnaire consisting of six questions related to medication use and safety (how to get, use, store, and dispose medicines) was utilized to assess the level of children’s knowledge. There was a significant difference between levels of knowledge before and after the program (p < 0.05) although some schoolchildren already had good baseline knowledge of medications. This local initiative may contribute to improving medication awareness, so more educational programs using colourful visuals and interactive games may be conducted with this vulnerable population as children will bring their medication-taking behaviour throughout their adult lives.